Two Chinese Herbal Regimens Safe for the Elderly on Inhibiting Liver and Bladder Tumor Cell Growth and Regulating Gene Expression - Ruey-Shyang Chen; Min-Chi Lu; Shulhn-Der Wang; Huang-Shui Ke; Ru-Hsiu Teng; Yu-Lin Kao; Chia-Cheng Kuo; Shung-Te Kao; Yun-Wei Lin; Biehuoy Shieh; Ching Li; Hui-Fen Liao (International Journal of Gerontology, 2011)
Background: Cancers have become one of the most lethal diseases in elders. In traditional Chinese medicine, Tan-Chih-Hsiao-Yao-San (TCHYS) and Long-Daan-Shiah-Gan-Tang (LDSGT) are used to treat cancers. However, the growth-inhibitory effects and gene expression profiles of these drugs on cancer cells are still unclear. Methods: This study assessed the effects of TCHYS and LDSGT on viability of liver and bladder tumor cells, and bladder TCCSUP cells were further subjected to profile gene expression patterns with microarray technology for identifying gene candidates that may be involved in the tumorigenesis. Results: The results revealed that both drugs significantly eliminated the growth of Chang liver and three hepatoma cells. On the contrary, the embryonic liver WRL68 cells showed less response to the treatments, whereas the control agent genistein had much higher inhibitory effect in WRL68 cells than in the other hepatoma cells. Both TCHYS and LDSGT, as well as cisplatin and paclitaxel, exhibited dose-dependent suppression on the viability of all bladder cancer cells. To characterize the possible regulation for such effects, the profiling of gene expression was performed with complementary DNA chips. When bladder transitional cell carcinoma (TCC) TCCSUP cells were treated with TCHYS, 29 upregulated and 28 downregulated genes were detected; whereas 54 genes were upregulated in the same cells treated with LDSGT. Moreover, the detected gene expression patterns were also confirmed by using the reverse transcription-polymerase chain reaction assay. Conclusion: This study initiates the evaluations of drug efficacies and gene expression profiles of traditional Chinese medicines, which may provide important information and identify useful biomarkers for treating cancers.